PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN DISIPLIN KERJA TERHADAP KINERJA PETUGAS AVSEC DI BANDAR UDARA ADI SOEMARMO SOLO - Muhammad Febriansyah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The company's motivation to accomplish its objectives comes from the performance of its employees. Avsec officers at Adi Soemarmo Airport deal with a number of issues pertaining to work discipline and human resource quality in the course of their duties. Researchers found that several workers lacked job discipline, professionalism, and collaboration. The primary emphasis of research is this issue in order to comprehend how work discipline and the caliber of human resources affect output.The research was carried out from February 1 to March 31, 2024. This study uses a quantitative method. The sample in the study was 82 Avsec officers. The data collection technique used a questionnaire distributed to 82 respondents. The collected data were analyzed using validity test, reliability test, normality test, heterokedasticity test, multicollinearity test, T test, F test, multiple linear regression analysis, and determination coefficient. The study’s findings indicate that the work discipline and human resource quality variables have a partial impact on Avsec officers’ performance. A T test with a variable's sig value less than 0.05 was used to obtain this. Work discipline and human resource quality have a simultaneous impact on performance, according to the F test results. An adjusted r-square of 0.558 was calculated based on the determination coefficient. This indicates that 44.2% of the variation in officer performance was due to other factors, while the remaining 55.8% was impacted by the variables of work discipline and human resource quality